Outsourcing candidate selection: The fight against clientelism in East Asian parties. (January 2014) - Hellmann, Olli
Conflict between factions has been identified as an important factor explaining different procedures of candidate selection. However, the question of what drives factions in choosing certain procedures over others remains under-theorized. This article argues that, when ranking their preferences for candidate selection procedures, factions are influenced by their electoral strategy. While clientelistic factions will push for candidate selection procedures that subordinate themselves to the logic of clientelistic exchange networks, programmatic factions will try to maximize the effectiveness of formal regulations. To demonstrate this relationship, the article studies the recent development of political parties in Taiwan and South Korea, where programmatic factions have 'outsourced' the authority to nominate candidates to external actors, thereby moving it beyond the reach of internal patron–client networks.